Surgical treatment of anal stenosis: assessment of 77 anoplasties Tratamento cirúrgico da estenose anal: resultados de 77 anoplastias - Angelita Habr-Gama; Carlos Walter Sobrado; Sergio Eduardo Alonso de Araújo; Sergio Carlos Nahas; Ingrid Birbojm; Caio Sergio Rizkallah Nahas; Desidério Roberto Kiss (Clinics, 2005)
PURPOSE: Anal stenosis is a rare, incapacitating, and challenging condition, occurring mainly after hemorrhoidectomy, for which several surgical techniques have been devised. The purpose of this study was to describe early and late (1 year) results of 77 anoplasty operations performed in the Colorectal Unit of our institution. METHODS: From 1977 to 2002, 77 patients with moderate to severe anal stenosis underwent surgery using two sliding graft techniques: 58 underwent Sarner's operation and 19 underwent Musiari's technique. Bilateral flaps were used in 7 patients. RESULTS: Early morbidity was due to pruritus occurring in 2 patients, urinary infection in 1, and temporary incontinence in 1 patient. One patient needed early reoperation following suture line dehiscence. Late results (1 year) were classified as good in 67 cases (87%). There was no reoperation due to recurrence of stenosis. CONCLUSION: The ease of performance, good functional results, and lack of severe complications show that Sarner's and Musiari's flap advancement techniques are effective and safe methods for surgical correction of anal stenosis, particularly when cutaneous fibrosis plays a major role in its etiology. OBJETIVO: A estenose anal é uma condição rara, incapacitante e desafiadora que ocorre principalmente após hemorroidectomia, para a qual diversas técnicas cirúrgicas reparadoras foram desenvolvidas. O objetivo deste estudo é descrever os resultados precoces e tardios (um ano) de 77 anoplastias realizadas no Serviço de Cirurgia Colorretal. MÉTODOS: No período de 1977 a 2002, 77 pacientes com estenose anal moderada ou grave foram operados, utilizando-se duas técnicas diferentes de avanço de retalho: 58 foram submetidos à técnica de Sarner e 18 submetidos à Técnica de Musiari. Avanços bilaterais foram utilizados em sete pacientes. RESULTADOS: As complicações precoces foram: prurido em dois pacientes, infecção urinária em um paciente e incontinência fecal temporária em outro. Um paciente necessitou reoperação precoce por deiscência de linha de sutura. Os resultados tardios foram classificados como bons em 67 (87%). Não houve reoperação por recorrência de estenose. CONCLUSÃO: A facilidade técnica, os bons resultados funcionais e a ausência de complicações graves demonstraram que as técnicas de avanço de retalho de Sarner e Musiari são efetivas e seguras para correção de estenose anal, particularmente nos casos em que a fibrose cutânea é o principal fator etiológico.